Effects of rescaling the EU energy label on household preferences for top-rated appliances - Corinne Faure; Marie-Charlotte Guetlein; Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
The European Union has decided to replace its current A+++ to D labelling scheme for cold appliances with a rescaled A to G labelling scheme. Employing a demographically representative discrete choice experiment on refrigerator adoption using an online survey among more than 1000 households in Germa-ny, this paper explores the effects of the rescaled scheme compared to the old scheme on the stated uptake of top-rated refrigerators. Since in practice both schemes will be shown for a transitory period, the paper also analyses the ef-fects of displaying both labels simultaneously. The findings from estimating a mixed logit model suggest that showing the rescaled A to G label alone signifi-cantly increases valuation of top-rated refrigerators compared to showing the current A+++ to D label alone. In comparison, when the A+++ to D and the re-scaled A to G schemes are shown simultaneously, no benefits of introducing the rescaled label are found. Thus, policymakers should strive to enforce the application of the rescaled label scheme as quickly as possible and to shorten transitory periods where both labels are shown simultaneously.
urn:nbn:de:0011-n-6057479
Keywords: 330; energy efficiency; energy label; appliances; choice experiment